2017
DOI: 10.1680/jgere.16.00015
|View full text |Cite
|
Sign up to set email alerts
|

Case studies to demonstrate challenges of driven piles on rock

Abstract: 2In Wyoming, pile foundations for bridges are often driven on rock materials because of the state's shallow bedrock stratigraphy. Unfortunately, no static analysis methods are currently available for estimating the resistance of these driven piles. In this paper, two recently completed bridge projects (the Owl Creek and Woods Wardell sites) on steel H-piles in Wyoming are explicitly presented, and data from three past projects are included to highlight the limited knowledge and challenges pertaining to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Pile resistances estimated using the signal-matching method from the CAse Pile Wave Analysis Program (CAPWAP) vary significantly with the resistances predicted using existing SA methods for driven piles in IGMs ( 3 ). Additionally, it has been observed that the pile resistances predicted for IGMs using current SA approaches vary from those found by dynamic load testing (DLT) ( 1113 ). The prediction of pile resistances in soft rocks using twenty static pile load trials did not yield any applicable prediction equations, either ( 3 ).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Pile resistances estimated using the signal-matching method from the CAse Pile Wave Analysis Program (CAPWAP) vary significantly with the resistances predicted using existing SA methods for driven piles in IGMs ( 3 ). Additionally, it has been observed that the pile resistances predicted for IGMs using current SA approaches vary from those found by dynamic load testing (DLT) ( 1113 ). The prediction of pile resistances in soft rocks using twenty static pile load trials did not yield any applicable prediction equations, either ( 3 ).…”
mentioning
confidence: 93%
“…If IGM is treated as soil, construction concerns, such as early pile refusal and pile breakage, might occur because of a lack of suitable design approaches and static pile load test data ( 11 ). The results of an investigation by Ng and Sullivan on fifteen steel piles driven into IGMs in Wyoming revealed that the current SA techniques designed for soils produced inconsistent and conservative predictions of geotechnical resistances ( 12 ). Pile resistances estimated using the signal-matching method from the CAse Pile Wave Analysis Program (CAPWAP) vary significantly with the resistances predicted using existing SA methods for driven piles in IGMs ( 3 ).…”
mentioning
confidence: 99%
“…In the next paper, Ng and Sullivan (2017) studied the common practice in Wyoming, USA where steel H-piles are driven to penetrate rock materials. Current static analysis methods, originally developed for soil, provided inconsistent and potentially conservative geotechnical resistance estimations for a driven pile on soft rocks.…”
mentioning
confidence: 99%